Corruption and Political Stability: Does the Youth Bulge Matter? - Mohammad Reza Farzanegan; Stefan Witthuhn (Center for Economic Studies and ifo Institute (CESifo), 2016)
This study shows that the relative size of the youth bulge matters for how corruption affects the internal stability of a political system. We argue that corruption cannot buy political stability (e.g., the greasing hypothesis) in countries with a relatively large youth population. Using panel data covering the 2002-2012 period for more than 100 countries, we find a negative interaction effect between the relative size of the youth population and corruption on internal political stability. Corruption is a destabilizing factor for political systems when the share of the youth population in the adult population exceeds a threshold level of approximately 19%. The negative interaction term is robust, controlling for country and year fixed effects, a set of control variables that may affect internal political stability, an alternative operationalization of youth bulge, and a dynamic panel estimation method.
Keywords: D73; D74; E02; H56; J11; 330; demographic transition; youth bulge; political stability; corruption